2017
DOI: 10.1080/15504263.2017.1319585
|View full text |Cite
|
Sign up to set email alerts
|

Improved Depressive Symptoms in Adults with Schizophrenia During a Smoking Cessation Attempt with Varenicline and Behavioral Therapy

Abstract: Depressive symptoms declined in adults with schizophrenia during 12 weeks of varenicline treatment and cognitive behavioral therapy, independent of tobacco abstinence. Smokers with SSD who have significant depressive symptoms may be successful in smoking cessation attempts with pharmacotherapeutic aids such as varenicline while maintaining stable psychiatric symptoms. This is a secondary analysis of data collected as part of a clinical trial registered as NCT00621777, at www.clinicaltrials.gov .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
0
4
0
2
Order By: Relevance
“…Moreover, there is evidence that quitting smoking is associated with recovery in stress, anxiety and depression in smokers. 44 54 55 A significant and progressive improvement of anxiety and depression was also reported in an observational study, and the protective effect was observed regardless of the presence of psychiatric pathology. 49 Many studies demonstrated gender differences in varenicline efficacy for smoking cessation 56 57 ; some studies also found a difference in neuropsychiatric events between genders.…”
Section: Main Findings and Interpretationmentioning
confidence: 72%
See 2 more Smart Citations
“…Moreover, there is evidence that quitting smoking is associated with recovery in stress, anxiety and depression in smokers. 44 54 55 A significant and progressive improvement of anxiety and depression was also reported in an observational study, and the protective effect was observed regardless of the presence of psychiatric pathology. 49 Many studies demonstrated gender differences in varenicline efficacy for smoking cessation 56 57 ; some studies also found a difference in neuropsychiatric events between genders.…”
Section: Main Findings and Interpretationmentioning
confidence: 72%
“…Of note, our result is consistent with another cohort study based on data from the general practice that a declined depression were observed to be associated with varenicline (HR 0.88, 95% CI 0.77 to 1.00) 30 ; similar finding was also reported in a clinical trial. 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Un estudio norteamericano con 14 pacientes psiquiátricos internados mostró que no hubo alteración en la incidencia de contención física o mecánica después de la implementación de la prohibición de fumar (27) .…”
Section: Discussionunclassified
“…Algunos estudios identificaron beneficios para los pacientes psiquiátricos con el tratamiento de la dependencia del tabaco como: mejoría de la salud mental; reducción de los síntomas depresivos, y disminución de la dosimetría de antipsicóticos y antiparkinsonianos (27) .…”
Section: Discussionunclassified